2021
DOI: 10.18009/jcer.900695
|View full text |Cite
|
Sign up to set email alerts
|

How does Information and Communications Technology Influence Turkish Students’ Science Achievement?

Abstract: This study aims to evaluate the science achievements of Turkish students based on 2018 PISA data both according to Information and Communications Technology (ICT) variables of student and school levels. With a relational research model, regression analysis was used to measure the variance factors affecting science achievement. Also, two-level Hierarchical Linear Modelling (HLM) analysis was used to add school-level analysis. According to the results, it can be said that student-level ICT variables explain appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
“…In those adolescents who are supervised in the use of ICT by their families and, in addition, use ICT as a methodological resource in schools, there are benefits in their academic performance [15,16,36,45]. However, those who use electronic tools and devices without supervision, as a means of recreation, socializing, or sharing multimedia images [13], decline in terms of their performance in mathematics, science, and reading comprehension [5,49]. This is a clear example of how certain factors influence students' ICT use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difficulty further diminishes the interests and desires of students who struggle with learning. Consequently, students tend to develop a negative attitude towards the course, teacher, and school (Karamustafaoğlu & Kaya, 2013;Kaya & Elgün, 2015). A negative attitude towards school and course can also adversely impact the learning process.…”
Section: Introductionmentioning
confidence: 99%